Talpa altaica Nikolsky 1883 - Rainer Hutterer (Smithsonian Institution Press, 1993)
Talpa altaica Nikolsky, 1883. Trans. Soc. Nat. St. Petersburg, 14:165. TYPE LOCALITY: Siberia, Altai Mtns, Valley of Tourak. DISTRIBUTION: Taiga zone of Siberia between Ob and Lena rivers; south to N Mongolia. COMMENTS: Placed by Yudin (1989:52) in genus Asioscalops; but see Corbet (1978c:33). Kratochvll and Krâl (1972) provided karyological evidence for a separation of altaica from the remaining Talpa species. Published as part of Rainer Hutterer, 1993, Order Insectivora, pp. 69-130 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 128, DOI: 10.5281/zenodo.7353085